2021
DOI: 10.1038/s41598-021-87763-1
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH4 promotes tumourigenesis with a poor prognosis in non-small-cell lung cancer

Abstract: The human AlkB homolog family (ALKBH) of proteins play a critical role in some types of cancer. However, the expression and function of the lysine demethylase ALKBH4 in cancer are poorly understood. Here, we examined the expression and function of ALKBH4 in non-small-cell lung cancer (NSCLC) and found that ALKBH4 was highly expressed in NSCLC, as compared to that in adjacent normal lung tissues. ALKBH4 knockdown significantly induced the downregulation of NSCLC cell proliferation via cell cycle arrest at the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Interestingly, it has been reported that the ALKBH1 mRNA and protein expression levels differ in gastric cancer (16). According to our previous study, the ALKBH4 mRNA and protein expression levels were higher in LUAD and LUSC than in normal tissues (14). The current study revealed that the expression of ALKBH4 protein was also higher in NSCLC than in normal tissues.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Interestingly, it has been reported that the ALKBH1 mRNA and protein expression levels differ in gastric cancer (16). According to our previous study, the ALKBH4 mRNA and protein expression levels were higher in LUAD and LUSC than in normal tissues (14). The current study revealed that the expression of ALKBH4 protein was also higher in NSCLC than in normal tissues.…”
Section: Discussionsupporting
confidence: 57%
“…Pilžys et al (39) reported that the silencing of ALKBH4 markedly decreased HeLa cancer cell survival. We have previously shown that ALKBH4 promotes the progression of lung cancer via E2F1 (14), which plays an important role in cell cycle progression, senescence and apoptosis (40)(41)(42). As mentioned above, the ALKBH family is associated with the progression of various cancers by playing a multifunctional role.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…ALKBH proteins could reverse N-methylation in DNA and RNA, and play potential roles in cancers as a group [18,19]. Recently an increasing body of evidence suggested that the ALKBH family promoted tumorigenesis and might be a potential target for novel anticancer therapy [20][21][22]. There are nine members of the ALKBH family in humans.…”
Section: Discussionmentioning
confidence: 99%